Heat shock protein 90 inhibitors repurposed against Entamoeba histolytica - Shahinas, Dea; Debnath, Anjan; Benedict, Christan; McKerrow, James H.; Pillai, Dylan R. (Frontiers in Microbiology, 2015)
Hsp90 is an essential chaperone responsible for trafficking a vast array of client proteins, which are substrates that Hsp90 regulates in eukaryotic cells under stress conditions. The ATP-binding N-terminal domain of Hsp90 (also known as a GHKL type ATPase domain) can serve as a specific drug target, because sufficient structural diversity in the ATP-binding pocket of Hsp90 allows for ortholog selectivity of Hsp90 inhibitors. The primary objective of this study is to identify inhibitors specific for the ATP-binding domain of Entamoeba histolytica Hsp90 (EhHsp90). An additional aim, using a combination of site-directed mutagenesis and a protein in vitro assay, is to show that the antiparasitic activity of Hsp90 inhibitors is dependent on specific residues within the ATP-binding domain. Here, we tested the activity of 43 inhibitors of Hsp90 that we previously identified using a high-throughput screen. Of the 43 compounds tested, 19 competed for binding of the EhHsp90 ATP-binding domain. Five out of the 19 EhHsp90 protein hits demonstrated activity against E. histolytica in vitro culture: rifabutin, rutilantin, cetylpyridinium chloride, pararosaniline pamoate and gentian violet. These 5 top E. histolytica Hsp90 inhibitors showed 30-100% inhibition of E. histolytica in culture in the micromolar range. These data suggest that E. histolytica-specific Hsp90 inhibitors are possible to identify and provide important lead compounds for the development of novel antiamebic drugs.